2016
DOI: 10.1016/j.jpain.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Prescription Opioid Overdose Among Colorado Medicaid Beneficiaries

Abstract: This article presents the risk factors of opioid overdose among the Colorado Medicaid population. On the basis of study findings, Colorado Medicaid is currently working with physicians, hospitals, and other health system stakeholders to continue to develop policies to identify and assist this subset of our population. One such policy will be to provide at-home intranasal naloxone for overdose rescue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 13 publications
3
41
1
2
Order By: Relevance
“…Bivariate and multivariate results indicate that having ever overdosed was associated with regular nonmedical benzodiazepine use among this group of young adult nonmedical opioid users; this is consistent with the results of Dilokthornsakul et al (2016) and Dietze et al (2005) who found that using benzodiazepines in conjunction with opioids at a minimum doubled the risk for overdose. Our findings affirm those of other studies that demonstrate heightened risk for overdose when benzodiazepines are used concurrently with opioids (Chan et al, 2006; Jann et al, 2014; Jones et al, 2015; Kerr et al, 2007; McGregor et al, 1998; Toblin et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Bivariate and multivariate results indicate that having ever overdosed was associated with regular nonmedical benzodiazepine use among this group of young adult nonmedical opioid users; this is consistent with the results of Dilokthornsakul et al (2016) and Dietze et al (2005) who found that using benzodiazepines in conjunction with opioids at a minimum doubled the risk for overdose. Our findings affirm those of other studies that demonstrate heightened risk for overdose when benzodiazepines are used concurrently with opioids (Chan et al, 2006; Jann et al, 2014; Jones et al, 2015; Kerr et al, 2007; McGregor et al, 1998; Toblin et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…The nonmedical use of benzodiazepines among opioid users is a serious concern as benzodiazepines can markedly increase the harmful effects of opioids, particularly risk for fatal and non-fatal overdose (Chan, Stajic, Marker, Hoffman, & Nelson, 2006; Dietze, Jolley, Fry, & Bammer, 2005; Dilokthornsakul et al, 2016; Jann, Kennedy, & Lopez, 2014; Jones & McAninch, 2015; Kerr et al, 2007; Perret, Deglon, Kreek, Ho, & La Harpe, 2000; Toblin, Paulozzi, Logan, Hall, & Kaplan, 2010; White & Irvine, 1999). While opioids are the most common drug class involved in overdose, most overdoses involve more than one substance (McGregor, Darke, & Christie, 1998; Oliver & Keen, 2003; Ward & Barry, 2001; Wunsch, Nakamoto, Behonick, & Massello, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These limitations are persistent in the literature. We reviewed 6 additional opioid safety studies that were published after the CDC guidelines (until December 31, 2016) and 1 study previously published but not cited in the guidelines; these studies shared similar limitations …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…One of the leading causes of death in this population is opioid overdose (Degenhardt, Larney, Randall, Burns, & Hall, 2014;Stenbacka, Leifman, & Romelsjo, 2010). There is extensive knowledge about possible risk factors for overdose such as, being outside of drug-treatment, older age, depression, length of injecting career and combining opioid injections with alcohol and/or benzodiazepine use (Bartoli et al, 2014;Bohnert, Roeder, & Ilgen, 2011;Clausen, Anchersen, & Waal, 2008;Dilokthornsakul et al, 2016;Jones & McAninch, 2015;Riley et al, 2016;Wichmann, Nielsen, Siersma, & Rasmussen, 2013;Winstanley & Clark, 2015). Despite this knowledge, mortality rates due to overdose remain high in many developed countries (Emcdda, 2015).…”
Section: Introductionmentioning
confidence: 99%